Manajemen Risiko Kecelakaan Kerja Menggunakan Metode FMEA Pada Proyek Pembangunan Gedung At-Taawun Universitas Muhammadiyah Surabaya - CHOIRUDDIN, HILMAWAN (Universitas Negeri Surabaya, 2023)
Construction project is an activity carried out with a complex development process and requires time that can occur problems and obstacles as well as various risks. One of the risks that can occur is the risk of work accidents that can affect the process of implementing project development. Efforts that can be made to minimize and prevent the occurrence of risks are by carrying out work accident risk management. Risk management carried out in this study is on the At-Taawun building construction project at Muhammadiyah University of Surabaya used is using the FMEA method. The research method used is quantitative descriptive research. Data collection techniques used by conducting observations, interviews, distributing questionnaires and literature studies. The results showed that there are 3 work accident risks that have a high risk value from 14 dominant work accident risks that can occur. 3 risks with the highest RPN value have a value of 36, namely the risk of workers being exposed to concrete splashes during piling, workers' eyes being exposed to fine dust from iron and workers being electrocuted due to an electrical short circuit.